SHIFT IN FAMILY SOCIAL VALUES DUE TO CHANGES IN ECONOMIC STRUCTURE - Syahwanes, Adnin Chiesa; Maylawati, Windi (LPPM Universitas Bina Bangsa, 2025)
This research examines shifts in social values ​​in families that occur due to changes in economic structure. Through a descriptive approach and literature review, this study analyzes 50 journals published in the 2015-2025 period, consisting of national and international journals that can be accessed online. The research results show that changes in economic structure characterized by industrialization, urbanization, economic digitalization, and the entry of women into the formal labor market have triggered a significant transformation in family values. These value shifts include: firstly, a reorientation of traditional gender roles, secondly changes in parenting patterns, thirdly modifications to the family hierarchy to become more egalitarian, fourthly a shift in the concept of independence versus dependence between family members, and fifthly a redefinition of family success which is increasingly oriented towards material aspects. This research also identified variations in value shifts based on socio-cultural context, education level, and family socio-economic status. This study contributes to a comprehensive understanding of the dynamics of social change in family institutions as an adaptive response to broader economic structural transformations, and highlights the importance of policies that align economic needs with the preservation of positive family values.